Assessing small livestock herders’ adaptation to climate variability and its impact on livestock losses and poverty - Faisal, Muhammad; Abbas, Azhar; Xia, Chunping; Haseeb Raza, Muhammad; Akhtar, Shoaib; Arslan Ajmal, Muhammad; Mushtaq, Zulqarnain; Cai, Yi (Climate risk management, 2021)
Livestock has a considerable role in the well-being of poor rural households in many developing countries. On the other hand, its productivity is adversely affected by climatic changes mainly due to the absence or non-adoption of effective and modern mitigation and adaptation strategies. The geographical locations and socio-economic conditions of developing countries make livestock herders, especially the smaller ones, more vulnerable while their capabilities to mitigate the adverse effects with limited resources will exacerbate the situation in the future. Most of the efforts to face climatic changes are directed at crop sector while only a few studies document such actions to safeguard livestock sector with similar focus notwithstanding the huge impact of these stimuli on this sub-sector of agriculture. This study uses propensity score matching (PSM) to assess the causal impact of climate change adaptation strategies on livestock losses and poverty by using the primary data set of 405 small livestock herders of Punjab, Pakistan. The PSM analysis points towards a massive potential for reducing these losses. The livestock losses and poverty index are shown to decline respectively by 30–48% and 4–22% for the farmers adopting a mix of mitigation strategies. Such outcome is believed to sustain environment and livestock herders’ well-being. Results indicate that livestock herders easily adopt those strategies that have greater linkages with accessibility and resource availability. Study reveals the significance of improving infrastructure for speedy access to information, resources and uninterrupted flow of veterinary services. The vet personnel also need to be equipped with precise statistics of disease existence, impacts, dispersal, and costs for control by restructuring and advancing data collection efforts that would entail coherent policy formulation amidst evidence-based outcomes. The results do imply allocation of huge investment in the information delivery system; competitive institutional services and particular safeguarding of the resource-poor farmers to sustain livelihoods, food security and rural development.